2006
DOI: 10.1007/s00595-006-3294-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Resection of an Ileal Lipoma: Report of a Case

Abstract: A 63-year-old woman was admitted to our hospital for investigation of upper abdominal pain and vomiting. Ultrasonography (US) showed a hyperechoic mass in the right lower abdomen, and computed tomography (CT) showed a low-density mass and intestinal invagination. Thus, we made a diagnosis of intestinal lipoma with intussusception and performed laparoscopic partial resection of the ileum, including the tumor. The resected specimen contained a round tumor, 25 x 22 x 20 mm, which was identified as an intestinal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 13 publications
0
26
0
3
Order By: Relevance
“…Surgical resection, including laparoscopic surgery, is a common treatment for lipomas of the small bowel [16]. A PubMed search for the last 10 years yielded only 2 reports of patients with lipomas in the small intestine treated with endoscopic resection; one was a giant ileal lipoma treated with endoscopic unroofing submucosal dissection [11], and the other was a lipoma of the jejunum removed by endoscopic resection using an SB knife.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection, including laparoscopic surgery, is a common treatment for lipomas of the small bowel [16]. A PubMed search for the last 10 years yielded only 2 reports of patients with lipomas in the small intestine treated with endoscopic resection; one was a giant ileal lipoma treated with endoscopic unroofing submucosal dissection [11], and the other was a lipoma of the jejunum removed by endoscopic resection using an SB knife.…”
Section: Discussionmentioning
confidence: 99%
“…Akut appendisit şüphesi olan hastalarda laparoskopik eksplorasyon sayesinde mevcut veya eşlik eden diğer patolojilerin tanı ve tedavisi de mümkün olmaktadır. [15] Biz de olgumuzda laparasopik eksplorasyon esnasında torsiyone lipomu tespit ederek, sadece iki trokar girişi kullanarak lezyonun eksizyonunu gerçekleştirdik.…”
Section: Discussionunclassified
“…In the present case, the patient underwent laparoscopic ileocecal resection by RPS and showed no complications or recurrence during 8 months follow up after surgery. The use of laparoscopic surgery for benign bowel tumors and ileocecal intussusception has recently increased [13][14][15][16][17] . Namikawa et al 12 reported that cases of short-duration adult intussusception, even at colonic sites, could be effectively treated by preoperative reduction followed by minimally invasive surgery using laparoscopy, avoiding extensive and invasive resection.…”
Section: Discussionmentioning
confidence: 99%